SOCIAL AND RELIGIOUS VALUES IN WEDDING PARTIES IN NORT MALUKU - Bahagia; Leni Muniroh; Abdul Karim Halim; Ritzkal; Rimun Wibowo; M. Azhar Al-Wahid; Siti Rahma Bahrain (al-Afkar, Journal For Islamic Studies, 2022)
The tradition includes culture and customs carried out in a particular society. One of the traditions and cultures that is applied to weddings in North Maluku. The purpose of this study is to find social values ​​including the value of cooperation. Another goal is to find the link between religious values ​​and marriage traditions. At the same time knowing how the wedding event from the beginning to the wedding. The research method used is the descriptive qualitative method. Meanwhile, the sampling method used a purposive technique. Meanwhile, data collection was carried out in various ways including observation, documentation, and in-depth interviews. The results of the study show that the marriage tradition in North Maluku contains the value of gotong royong or working together to realize public activities. The term giving goods to those who want to get married is called basolo. While catfish in weddings belong to people who deliver food, rice, and fruit and help chop wood. Residents also help in making tents and cooking food and drinks. Religiously, in marriage there must be religious values, namely, there is a marriage contract which is a pillar of marriage and marriage is part of religion, there are also guardians who are part of the pillars of religion. The marriage culture in North Maluku is very thick with customs. Weddings have been carried out since ancient times, starting from the system of proposing to the bridegroom's family welcome ceremony and the bride's family, then the agreement to the wedding procession. North Maluku is a traditional country founded by four kingdoms, namely the kingdoms of Ternate, Jailolo, Tidore, and Bacan called "moloku kieraha".